Numerical simulation of moisture transport along ceramic brick interfaces. - Araújo, Camila Mota de (2022)
Moisture transport in brick masonry is an important phenomenon in various deterioration mechanisms. However, it is a very complex process and is influenced by many physical phenomena. The investigation of moisture transfer through a building wall, which in general consists of multiple layers, presupposes knowledge about the continuity between the layers. In this study, two types of contact configurations were analyzed, as follows: Perfect Hydraulic Contact and Air Space Interface. Therefore, to understand moisture transport in brick masonry, moisture transport through the materials' interface was analyzed. This was done for cement mortar and brick samples, lime mortar and brick samples, and samples with air space between brick layers, as well as for samples with different interface location heights and different air space thicknesses. Mainly, the present work aims to simulate the hygrothermal behavior through brick-mortar and brick-brick interfaces in samples with perfect hydraulic contact and with air space between brick layers to compare the results with laboratory analyses. The numerical simulations of brick-mortar and brick-brick samples were performed with WUFI-2D hygrothermal simulation software. WUFI-2D is a computer program, based on the hygrothermal calculation model, which has at its base a coupled transport equation system and numerical solution technique, developed by Künzel (1995). The data used to run the simulations were extracted from water absorption tests on laboratory samples; the corresponding moisture content profiles were measured using gamma ray spectrometers. Although the mechanisms of moisture transport in a single building material have been and continue to be extensively studied, the hydraulic characteristics of the interface at different types of contacts between materials are still poorly understood and, for this reason, the simplified assumption of perfect hydraulic contact, is widely used in hygrothermal models. In general terms, the assumption of perfect hydraulic contact implies that the interface will have no effect on moisture transport. In comparison, the assumption of imperfect hydraulic contact implies that the interface between building materials will resist moisture transport. However, comparisons between the experimental and numerical results showed a large difference in the moisture transport behavior for samples with perfect hydraulic contact and imperfect hydraulic contact due to the influence caused by the interface.